2011
DOI: 10.1016/j.mce.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids and circadian clock control of cell proliferation: At the interface between three dynamic systems

Abstract: The circadian clock, an endogenous timekeeper that regulates daily rhythms of physiology, also influences the dynamic release of glucocorticoids. The release of glucocorticoids is characteristically pulsatile and is further modulated in a circadian fashion. A circadian pacemaker in the brain regulates daily rhythms of hypothalamicpituitary-adrenal axis and autonomic nervous system activity that both influence glucocorticoid release from the adrenal gland. This systemic regulation interacts with rhythms in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 178 publications
0
33
0
Order By: Relevance
“…Glucocorticoids promote synaptic development, neuronal plasticity (Liston and Gan 2011), and cell proliferation, and themselves have the capacity for resetting circadian oscillators in peripheral tissues (Balsalobre et al 2000a;Dickmeis and Foulkes 2011). Diurnal release of glucocorticoids occurs in synchrony with the animal's activity cycle (Dickmeis and Foulkes 2011).…”
Section: Mechanisms Linking the Circadian Clock And Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Glucocorticoids promote synaptic development, neuronal plasticity (Liston and Gan 2011), and cell proliferation, and themselves have the capacity for resetting circadian oscillators in peripheral tissues (Balsalobre et al 2000a;Dickmeis and Foulkes 2011). Diurnal release of glucocorticoids occurs in synchrony with the animal's activity cycle (Dickmeis and Foulkes 2011).…”
Section: Mechanisms Linking the Circadian Clock And Memorymentioning
confidence: 99%
“…Diurnal release of glucocorticoids occurs in synchrony with the animal's activity cycle (Dickmeis and Foulkes 2011). In mice, training during peak glucocorticoid levels increases learning-induced spine formation, while training during the circadian trough does not (Liston et al 2013).…”
Section: Mechanisms Linking the Circadian Clock And Memorymentioning
confidence: 99%
“…RORa is a nuclear receptor involved in both lipogenesis and lipid storage, which can activate Bmal1 transcription (26). Glucocorticoids (GC) and its receptor (GR) have also been identified as an important link between circadian clocks and nutrients (27). Studies have shown that liver-specific GR mutation display accelerated phase shifting in response to restricted feeding schedule in daytime (28), while injection of corticosterone do not cause the phase shifting induced by restricted feeding (29).…”
Section: The Connection Between Nutrients and Circadian Rhythmsmentioning
confidence: 99%
“…Glucocorticoids (GCs) are steroid hormones derived from the adrenal gland which function in a wide array of physiological processes, including inflammation, glucose homeostasis, and cell proliferation [68]. Their anti-inflammatory effects are exploited pharmaceutically to combat pain, allergies, arthritis as well as lymphomas and leukemia.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…The outcome of GC signaling is tissue-specific and likewise the effect of GC signaling in cancerous cells depends on the type; pro-apoptotic in certain cancers, but pro-survival and promoting resistance to cell death in others [68,74]. In obesity, GCs also have pleiotropic effects but generally promote fat deposition.…”
Section: Glucocorticoidsmentioning
confidence: 99%